Rupatadine is effective in the treatment of chronic spontaneous urticaria in children aged 2–11 years. Issue 1 (12th November 2015) - Potter, Paul; Mitha, Essack; Barkai, László; Mezei, Györgyi; Santamaría, Eva; Izquierdo, Iñaki; Maurer, Marcus
Abstract: Background: Recommendations in current guidelines for the treatment of chronic spontaneous urticaria (CSU) in infants and children are mostly based on extrapolation of data obtained in adults. This study reports the efficacy and safety of rupatadine, a modern H1 and PAF antagonist recently authorized in Europe for children with allergic rhinitis and CSU. Methods: A double‐blind, randomized, parallel‐group, multicentre, placebo‐controlled compared study to desloratadine was carried out in children aged 2–11 years with CSU, with or without angio‐oedema. Patients received either rupatadine (1 mg/ml), or desloratadine (0.5 mg/ml) or placebo once daily over 6 weeks. A modified 7‐day cumulative Urticaria Activity Score (UAS7) was employed as the primary end‐point. Results: The absolute change of UAS7 at 42 days showed statistically significant differences between active treatments vs. placebo (−5.5 ± 7.5 placebo, −11.8 ± 8.7 rupatadine and −10.6 ± 9.6 desloratadine; p < 0.001) and without differences between antihistamines compounds. There was a 55.8% decrease for rupatadine followed by desloratadine (−48.4%) and placebo (−30.3%). Rupatadine but not desloratadine was statistically superior to placebo in reduction of pruritus (−57%). Active treatments also showed a statistically better improvement in children's quality of life compared to placebo. Adverse events were uncommon and non‐serious in both active groups. Conclusion: Rupatadine is effective and well tolerated in the relief of urticaria symptoms, improving quality of life over 6 weeks in children with CSU. This is the first study using a modified UAS to assess severity and efficacy outcome in CSU in children.